"The "opinions of mortals" of Parmenides and a possible Eleatic Pythagoreanism - Cordero, Néstor Luis (Revista Archai, 2022)
The Goddess of Parmenides always announces that the glory are a human product. But there is one point that has not generally been noticed in the studies devoted to the study of theglory : they describe a human activity that consists in explaining reality by the presence of opposite principles, and that is always related to "nomination" (see fr. 8.51, fr. 8.38-41, fr 9, fr. 19.3). Was there a school in Parmenides' time which corresponded to this sketch, or is it a collage of Parmenides'? In any case, it is attested the presence of a branch of Pythagorism which was characterized, precisely, by "placing" names on things.